Nursing Management of Patients With Bowel Perforation: Assessment, Early Recognition, and Perioperative Care (The Review of Diabetic Studies, 2024)
Background: Bowel perforation is a critical surgical emergency characterized by full-thickness disruption of the gastrointestinal wall, leading to peritoneal contamination, systemic inflammation, and potential multiorgan failure. Early recognition and timely intervention are essential to reduce morbidity and mortality.Aim: To review the nursing management of patients with bowel perforation, emphasizing assessment, early recognition, and perioperative care strategies.Methods: This comprehensive review synthesizes current evidence on etiology, epidemiology, pathophysiology, clinical assessment, diagnostic evaluation, and management approaches. It highlights nursing roles in early detection, stabilization, and postoperative care through multidisciplinary collaboration.Results: Bowel perforation arises from diverse causes, including inflammatory conditions, obstruction, trauma, neoplasia, and iatrogenic injury. Clinical presentation varies from localized pain to diffuse peritonitis and septic shock. Diagnostic confirmation relies on imaging, particularly CT, supported by laboratory markers. Management prioritizes rapid resuscitation, broad-spectrum antibiotics, and timely surgical source control. Nonoperative strategies are reserved for stable patients with contained perforations. Postoperative care focuses on infection control, nutritional support, pain management, and complication prevention. Nursing vigilance in monitoring vital signs, abdominal changes, and early warning signs significantly improves outcomes.Conclusion: Effective management of bowel perforation requires prompt recognition, aggressive stabilization, and coordinated multidisciplinary care. Nurses play a pivotal role in early detection, perioperative support, and patient education, reducing complications and enhancing recovery.